Exoskeleton-Assisted Sit-to-Stand Training Improves Lower-Limb Function Through Modifications of Muscle Synergies in Subacute Stroke Survivors - Yang-An Li; Ze-Jian Chen; Chang He; Xiu-Pan Wei; Nan Xia; Ming-Hui Gu; Cai-Hua Xiong; Qin Zhang; Trisha M. Kesar; Xiao-Lin Huang; Jiang Xu (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2023)
Abnormal muscle synergies during sit-to-stand (STS) transitions have been observed post-stroke, which are associated with deteriorated lower-limb function and mobility. Although exoskeletons have been used in restoring lower-limb function, their effects on muscle synergies and lower-limb motor recovery remain unclear. Here, we characterized normal muscle synergy patterns during STS activity in ten healthy adults as a reference, comparing with pathological muscle synergy patterns in ten participants with subacute stroke. Moreover, we assessed the effects of a 3-week exoskeleton-assisted STS training intervention on muscle synergies and clinical scores in seven stroke survivors. We also investigated correlations between neuromuscular complexity of muscle synergies and clinical scores. Our results showed that the STS task involved three motor modules representing distinct biomechanical functions among healthy subjects. In contrast, stroke participants showed 3 abnormal modules for the paretic leg and 2 modules for the non-paretic leg. After the intervention, muscle synergies partially shifted towards the normal pattern observed in healthy subjects on the paretic side. On the non-paretic side, the synergy modules increased to three and neuromuscular coordination improved. Furthermore, the significant intervention-induced increases in Fugl-Meyer Assessment of Lower Extremity and Berg Balance Scale scores were associated with improved muscle synergies on the non-paretic side. These results indicate that the paretic side demonstrates abnormal changes in muscle synergies post-stroke, while the non-paretic side can synergistically adapt to post-stroke biomechanical deviations. Our data show that exoskeleton-based training improved lower-limb function post-stroke by inducing modifications in muscle synergies.